ACTIVITY BASED APPROACH IN DEVELOPING ESP STUDENTS’ COMMUNICATIVE COMPETENCE (Scientific journal of the Fergana State University, 2023)
The research article investigated the principles of activity-based approach in teaching English as a foreign language. The objectives of the study were to study the effective methods of activity-based approach in developing communicative competence of ESP students.